Comprehensive motion‐compensated highly accelerated 4D flow MRI with ferumoxytol enhancement for pediatric congenital heart disease. Issue 6 (9th December 2015) - Cheng, Joseph Y.; Hanneman, Kate; Zhang, Tao; Alley, Marcus T.; Lai, Peng; Tamir, Jonathan I.; Uecker, Martin; Pauly, John M.; Lustig, Michael; Vasanawala, Shreyas S.
Abstract : Purpose: To develop and evaluate motion‐compensation and compressed‐sensing techniques in 4D flow MRI for anatomical assessment in a comprehensive ferumoxytol‐enhanced congenital heart disease (CHD) exam. Materials and Methods: A Cartesian 4D flow sequence was developed to enable intrinsic navigation and two variable‐density sampling schemes: VDPoisson and VDRad. Four compressed‐sensing methods were developed: A) VDPoisson scan reconstructed using spatial wavelets; B) added temporal total variation to A; C) VDRad scan using the same reconstruction as in B; and D) added motion compensation to C. With Institutional Review Board (IRB) approval and Health Insurance Portability and Accountability Act (HIPAA) compliance, 23 consecutive patients (eight females, mean 6.3 years) referred for ferumoxytol‐enhanced CHD 3T MRI were recruited. Images were acquired and reconstructed using methods A–D. Two cardiovascular radiologists independently scored the images on a 5‐point scale. These readers performed a paired wall motion and functional assessment between method D and 2D balanced steady‐state free precession (bSSFP) CINE for 16 cases. Results: Method D had higher diagnostic image quality for most anatomical features (mean 3.8–4.8) compared to A (2.0–3.6), B (2.2–3.7), and C (2.9–3.9) with P < 0.05 with good interobserver agreement ( κ ≥ 0.49). Method D had similar or better assessment of myocardial borders and cardiac motion compared to 2D bSSFP ( P < 0.05, κ ≥ 0.77). All methods had good internal agreement in comparing aortic with pulmonic flow (BA mean < 0.02%, r > 0.85) and compared to method A (BA mean < 0.13%, r > 0.84) with P < 0.01. Conclusion: Flow, functional, and anatomical assessment in CHD with ferumoxytol‐enhanced 4D flow is feasible and can be significantly improved using motion compensation and compressed sensing. J. Magn. Reson. Imaging 2016;43:1355–1368.